Política Customizada de Balanceamento de Réplicas para o HDFS Balancer do Apache Hadoop - Fazul, Rhauani W.; Pitthan Barcelos, Patricia (Anais do Workshop de Testes e Tolerância a Falhas (WTF), 2019)
Data replication is a fundamental mechanism of the Hadoop Distributed File System (HDFS). However, the way data is spread across the cluster directly affects the replication balancing. The HDFS Balancer is a Hadoop integrated tool which can balance the storage load on each machine by moving data between nodes, although its operation does not address the specific needs of applications while performing block rearrangement. This paper proposes a customized balancing policy for HDFS Balancer based on a system of priorities, which can be adapted and configured according to usage demands. The priorities define whether HDFS parameters, or whether cluster topology should be considered during the operation, thus making the balancing more flexible.